1996
DOI: 10.1007/bf00018712
|View full text |Cite
|
Sign up to set email alerts
|

Short-term changes in tidepools following two hurricanes

Abstract: Three tidepools in the rocky intertidal zone of coastal Maine, USA, were examined before and after the passing of two hurricanes : Gloria, in 1985, and Bob, in 1991 . Surface area was little changed in one pool, and reduced in a second pool that were formed from rock . Surface area increased significantly in a third pool that had a nonpermanent border. Sand deposition on the bottom of tidepools increased in three of the five pairs of observations, and sand was not present before or after storms in the other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…Fluctuations in suspended seawater particles and seabed sediment volumes also affect kelp communities 31 . In coastal rocky areas, natural phenomena such as river floods 11 12 , accumulation after storms 14 15 and sediment scour by strong water currents create sediment loads 32 33 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluctuations in suspended seawater particles and seabed sediment volumes also affect kelp communities 31 . In coastal rocky areas, natural phenomena such as river floods 11 12 , accumulation after storms 14 15 and sediment scour by strong water currents create sediment loads 32 33 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Changes in turbidity and seabed sediments also affect kelp forests. Pulsed sediment loads occurring from natural phenomena, e.g., river floods 11 12 , cliff erosion and runoff 13 , resuspension after storms 2 14 15 and artificial processes including construction and solid waste disposal 16 17 18 can inflict serious harm on these macrophyte species.…”
mentioning
confidence: 99%
“…To date most studies on rocky pool fish assemblages have been focused on revealing community structure, temporal and spatial pattern of their abundance, and/or recolonization process after catastrophic perturbations (Moring, 1996). These studies have demonstrated that despite the dynamic of rocky pools, intertidal rocky fishes make a successful use of these habitats either as a transitory usage during their juvenile phase or as a permanent residence during their entire life.…”
Section: Introductionmentioning
confidence: 99%
“…: productivité et respiration) des communautés (Vitousek et al 1997b, Jackson et al 2001, Hooper et al 2005. Celles-ci sont également touchées par d'autres perturbations qui sont liées aux changements climatiques tels que l'augmentation de la température (Schiel et al 2004, Keser et al 2005, Mieszkowska et al 2006, Haie et al 2011) ou l'action des vagues causée par de fortes tempêtes (Dayton et al 1992, Moring 1996, Byrnes et al 2011, qui sont prédites d'augmenter dans le futur (Easterling et al 2000 ou de fluctuer davantage vers des extrêmes (Kerr 2011). On peut déjà assister à des changements du nombre, de l'identité et de l'abondance des espèces que ce soit au niveau local qu'au niveau global (Vitousek et al 1997b, Tilman andLehman 2001).…”
Section: Introduction Généraleunclassified